2019
DOI: 10.1097/jnr.0000000000000277
|View full text |Cite
|
Sign up to set email alerts
|

Care Needs of Patients at the End of Life With a Noncancer Diagnosis Who Live at Home

Abstract: End-of-life stage and initial score on the Palliative Performance Scale were found to have a significant influence on the multidimensional care needs of patients with a noncancer diagnosis. Thus, healthcare professionals should assess patient care needs according to disease trajectory to provide continuous and holistic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The involvement of the family caregivers is valuable and implies management of digestive problems, balance of fluid and food intake, nutritional status and care of bedsores. Needs such as: fall risks, self-care capacity, instrumental activities of daily living, dementia, fecal and urinary incontinence are difficult to solve [86]. Compared with cancer patients, the non-malignant patient's needs are more complex: moderate and severe neurological issues, psychiatric problems, needs for assistance with defecation and bladder function and moderate and severe deterioration of vigilance (somnolent and comatose) [87].…”
Section: Family Caregivers For Home Care Recipients With Advanced Non-cancer Diseasesmentioning
confidence: 99%
“…The involvement of the family caregivers is valuable and implies management of digestive problems, balance of fluid and food intake, nutritional status and care of bedsores. Needs such as: fall risks, self-care capacity, instrumental activities of daily living, dementia, fecal and urinary incontinence are difficult to solve [86]. Compared with cancer patients, the non-malignant patient's needs are more complex: moderate and severe neurological issues, psychiatric problems, needs for assistance with defecation and bladder function and moderate and severe deterioration of vigilance (somnolent and comatose) [87].…”
Section: Family Caregivers For Home Care Recipients With Advanced Non-cancer Diseasesmentioning
confidence: 99%
“…28,29 Loss of self, through losing personal relations, memories, or possessions were also present for care home residents. 37 Anxiety and depression were symptoms commonly rated as moderate or severe in one paper. 43 A specialist palliative care service found anxiety was evident in all populations, however those with multimorbidity reported anxiety less frequently.…”
Section: Qualitative Interviews 9 (9)mentioning
confidence: 99%
“…It has been reported that when patients and their caregivers have multiple chronic conditions (Webbkamigad et al, 2020) and complex needs (Spckalingam et al, 2020), they require care for longer periods of time (Palmer et al, 2018;Zhao et al, 2019) and that those need to be provided by multi-dimensional support services (DeGraaf et al, 2020;Lee et al, 2019;Peters et al, 2018). Such patients would benefit from early needs assessments and easy access to low-threshold services (Spitzer et al, 2015).…”
Section: Integrating Competencies Between and Within Professionsmentioning
confidence: 99%
“…These include factors relating to the individual, their family and the society and environment they live in (Stanhope et al, 2015). This has led to complicated health and well-being needs, which professionals from just one sector have not been able to address (DeGraaf et al, 2020;Lee et al, 2019;Spitzer & Davidson, 2013). The result has been that patients and clients have received services that have been delivered by highly educated, but separate, professionals with different competencies, working in a complex, fragmented system.…”
Section: Introductionmentioning
confidence: 99%